Comparing learning outcomes: on-screen versus print reading - Osias Kit T. Kilag; Cyd C. Peras; Rainlee B. Echavez; Jodhel D. Suba-an; Maria Kris B. Obaner; Debra P. Mansueto (Science and Education, 2023)
This study aimed to investigate the differences between on-screen reading and print reading in terms of reading comprehension and retention. It also explored the impact of demographic factors on the relationship between reading modality and reading comprehension. A total of 120 participants completed reading tasks in both on-screen and print formats, and their comprehension and retention scores were recorded. The results showed that the print reading group outperformed the on-screen reading group in both comprehension and retention. In addition, participants who had more experience with on-screen reading demonstrated better reading comprehension regardless of the modality. However, no significant interactions were found between reading modality and any of the demographic factors. These findings have implications for educators and learners who rely on digital devices for reading and learning. It is suggested that print reading may be more effective for promoting reading comprehension and retention, although previous experience with on-screen reading may play a role in improving reading comprehension in the digital format. Further research is needed to explore the underlying mechanisms of these effects and to identify ways to optimize reading and learning experiences in both digital and print formats.